Fungi and cancer: unveiling the complex role of fungal infections in tumor biology and therapeutic resistance - Wanli Zhang; He Zhang; Yiru Gao; Jianjun Lei; Chenhao Suo (Frontiers in Cellular and Infection Microbiology)
Cancer remains one of the most significant causes of mortality across the world. Despite remarkable advancements made in early detection, therapeutic strategies, and the advent of immunotherapy in recent years, numerous challenges continue to hinder optimal outcomes. The development and progression of cancer are driven not only by genetic and epigenetic alterations within tumor cells but also by dynamic interactions occurring with the surrounding tumor microenvironment (TME). It is a highly complex milieu composed of tumor cells, non-tumor stromal cells, extracellular matrix components, immune cells, blood vessels, and diverse signaling molecules. Emerging evidence underscores the pivotal role of fungi in influencing cancer biology, including initiation, progression, immune evasion, and the modulation of TME. Fungi, which are omnipresent microorganisms, have traditionally been considered opportunistic pathogens. However, recent research highlights their broader impact on host immunity and their potential contributions to cancer pathogenesis. For instance, in patients with cancer, fungal infections not only exacerbate clinical complications but also create conditions conducive to tumor growth, metastasis, and immune escape by altering the immune microenvironment. In addition, fungal-derived metabolites and their interactions with host immune pathways can significantly modulate the efficacy of immunotherapies. These findings have spurred interest in exploring antifungal strategies as adjunctive approaches in cancer management, positioning antifungal therapy as a burgeoning area of oncological research. This review provides an in-depth exploration of the complex interplay between fungi and cancer. It examines the multifaceted role of fungal infections in tumor biology, the mechanisms through which fungi reshape the TME through immune modulation and their influence on immune-evasion strategies and therapeutic resistance. Furthermore, the potential for integrating antifungal therapies into comprehensive cancer treatment regimens has been highlighted, offering insights into novel avenues for improving patient outcomes.